All Days 2006
DOI: 10.2118/99281-ms
|View full text |Cite
|
Sign up to set email alerts
|

Deployed Smart Technologies Enablers for Improving Well Performance in Tight Reservoirs—Case: Shaybah Field, Saudi Arabia

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractIntelligent wells are becoming the buzz word in the oil and gas industry. Today the development and deployment of smart technologies are important drivers for improving well productivity and delaying early water or gas breakthrough in tight and challenging reservoirs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…In gas-coning situations an equalizer can significantly reduce GOR values. Salamy et al (2006) have reported a 50% reduction in GOR when an equalizer was deployed for a horizontal well in Shaybah Field. This field observation echoes the gas coning results in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In gas-coning situations an equalizer can significantly reduce GOR values. Salamy et al (2006) have reported a 50% reduction in GOR when an equalizer was deployed for a horizontal well in Shaybah Field. This field observation echoes the gas coning results in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…With high oil prices prevailing, producers are more willing than ever to buy advanced wellbore equipment to improve well performance (Salamy et al 2006;Lorentz et al 2006;Williamson et al 2000). Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These wells were extended to 2-to 3-km single-lateral horizontal wells by 2000, then to MRC multilateral (ML) wells by 2002, and to MRC ML wells equipped with hydraulic flow-control valves by 2004 (Salamy et al 2006). The drivers for increased reservoir contact and downhole control included lower unit-development costs, higher well productivity, higher cumulative-oil production before gas breakthrough, and control of production after breakthrough (Saleri 2002;Salamy et al 2006Salamy et al , 2008. Saudi Aramco has more recently embarked on extreme-reservoir-contact (ERC) wells with reservoir contact frequently exceeding 10 km by increasing both the number of laterals and their lengths.…”
Section: Maximum-and Extreme-reservoir-contact-wells Backgroundmentioning
confidence: 99%
“…Early studies involving production logs for more than 60 single horizontal wells of 1-km length showed average flow contribution from 85% of the horizontal section with a generally uniform flow profile (Saleri et al 2003). A significant contribution from laterals greater than 1 km in length is implied from performance data (Saleri et al 2003, Salamy et al 2008), but profile data for laterals drilled beyond this length, and in ML wells are sparse, with FCV installation precluding production logging in most instances. In addition, through the process of actuating valves in wells equipped with FCVs, dead laterals were discovered and were subsequently cleaned up (Al-Dossary et al 2012).…”
Section: Maximum-and Extreme-reservoir-contact-wells Backgroundmentioning
confidence: 99%